THE TRANSFORMATION OF POLITENESS STRATEGIES IN DIGITAL DISCOURSE: A PRAGMATIC ANALYSIS - Sarimsakova Shoira Ulugbek qizi (International Journal of Literature and Language Studies, 2026)
This article investigates how politeness strategies are changing in the digital age due to the rise of online communication. While traditional politeness relies on face-to-face cues like tone of voice and gestures, digital communication lacks these physical elements. Using a corpus of 45,000 words from academic and social media interactions, this article analyzes how people adapt. The results show that digital politeness is a highly structured system. Interlocutors systematically use emojis as pragmatic softeners to reduce the bluntness of text messages. Additionally, the study identifies chronemic hedging intentionally delaying responses as a new way to show respect for another person’s time.